Assessment of Age-Related Changes in Width of Female Pelvis. - Sumit Singh; Sourabh Chandra; Swati Bansal; Srishti; Aditya Negi; Akshita; Mehsar (Educational Administration: Theory and Practice, 2024)
Introduction: The female pelvis undergoes morphological changes throughout life, with particular emphasis on width, which can influence various physiological and clinical outcomes. This study aims to assess the age-related changes in pelvic width among women and their potential implications for health. Methods: A cross-sectional analysis was conducted on a sample of women aged 10 to 65 years. Pelvic width was measured at critical anatomical points—ASIS to Right SI joint and ASIS to Left SI joint—using radiographic imaging and 3D scanning techniques to ensure precision. Results: The findings reveal that pelvic width increases significantly from young adulthood to middle age, peaking between 40 and 50 years. This enlargement is likely associated with reproductive adaptations, as a wider pelvis facilitates childbirth. However, a gradual reduction in width was observed in women over 60 years, likely due to age-related bone resorption and hormonal changes, particularly the decline in estrogen post-menopause. The contraction of the pelvis in later life could lead to clinical consequences such as increased susceptibility to pelvic floor dysfunction, osteoporosis, and fractures, impacting mobility and quality of life in older women. Discussion: Understanding the dynamics of pelvic width throughout the lifespan is essential for anticipating health issues associated with aging. The findings emphasize the need for further research on interventions to mitigate the negative effects of pelvic narrowing in elderly women and preventative strategies for younger populations. Conclusion: This study underscores the importance of monitoring pelvic width as a part of women’s health assessments, offering valuable insights into how pelvic morphology changes with age and its potential clinical implications.